Experimental and numerical investigations of deformation and fracture mechanisms in double-sided incremental forming - Peng, Wenxuan (2022)
Incremental sheet forming (ISF) is a novel sheet forming technology, which has had a rapid development in the last two decades. ISF and the Single Point Incremental Sheet Forming (SPIF) processes have considerable advantages of low cost, high flexibility and adaptability in manufacturing small batch and customized products for automotive, medical and aerospace applications. The general ISF process only requires the use of a Computer Numerical Control (CNC) milling machine to control a semi-spherical tool traveling along a pre-defined toolpath to form a blank sheet on a dedicated fixture. Through continuous deformation by layers, the blank workpiece is incrementally deformed to the desired shape. However, there are shortcomings in terms of formability and accuracy in SPIF process as reported in literature. As a result, several variants are proposed and developed to overcome these SPIF limitations.